Business Intelligence Model for Decision Making in a MYPE in the Construction Sector (LACCEI, 2024)
The objective of the research is to design a business intelligence model for the decision-making process in a company in the construction sector. The type of research is applied, descriptive, qualitative. The population is made up of 7 areas of the company and 20 workers. Interviews and surveys validated by expert judgment will be applied. As a result, it was obtained that the business intelligence system significantly improved the quality of the information for the 4 areas in which it would be implemented, in addition, meeting time was reduced by 90%. The information collected was analyzed, and it was concluded that the design of BIS in the company has gone from being a cost to a competitive advantage, this being a necessary resource to meet the objectives of the organizations since it reduces time, improves the quality of information, and ensures optimal organizational decision-making. The estimated cost of the investment amounted to S/. 12920.